PENGARUH KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BANK MANDIRI (PERSERO) Tbk, AREA MANADO - SAID, MEGAWATI; Rumawas, Wilhelmina; Asaloei, Sandra Ingrid (JURNAL ADMINISTRASI BISNIS, 2017)
The continuity of the organization or company is determined by the existing human resources, both quality and quantity. Each organization has different objectives and in the implementation is done by employees. Employees are therefore a major factor in corporate activities. Each organization will basically have different policies on the human resources it has to achieve employee productivity. In the achievement that affects the productivity of employees there are many factors that affect work productivity, among others, is the existence of job satisfaction. With a sense of satisfaction in working the employee will show a good personal in the company, a positive performance that satisfies the company and arises willingness to work high level of work productivity for the interests of the company, and facilitate the achievement of corporate goals. Job satisfaction is an evaluation that describes a person for feeling his attitude, happy or not happy, satisfied or not satisfied in work The purpose of this study is to analyze the effect of job satisfaction on employee productivity at PT. Bank Mandiri (Persero) Tbk, Area Manado. Job Satisfaction is measured through five indicators, namely Jobs, rewards, supervision of superiors, co-workers, and promotional opportunities. This research is a quantitative research by using simple linear regression approach. Data collection techniques were done by distributing questionnaires filled by 39 respondents and analyzed using simple regression analysis and using test t test hypothesis. From the results of simple linear regression analysis of job satisfaction variables affect the productivity of employees of PT. Bank Mandiri (Persero) Tbk, Area Manado. And result of hypothesis test show that job satisfaction variable simultaneously have a significant effect to work productivity of PT. Bank Mandiri (Persero) Tbk, Area Manado. Based on the results of this study, the company can continue to facilitate employees in improving job satisfaction so that employee productivity can be achieved. . Keywords: Job Satisfaction, Work Productivity.